Two-dimensional materials and three-dimensional printing for electrochemical biosensing applications - Nasuha Rohaizad (Nanyang Technological University, 2021)
Two-dimensional (2D) materials and three-dimensional (3D) printing are promising technologies in advancing the development and commercialisation of electrochemical biosensors. 2D materials have been sought to enhance the sensitivity of biosensors due to their alluring large surface area that exposes more active sites as well as facilitates the immobilisation of biorecognition elements. This thesis aimed to delve into transition metal dichalcogenides (TMDs), a prominent class of 2D materials, for electrochemical biosensors. Different elemental compositions were scrutinised as unique properties were anticipated, specifically TMDs of group 4 (TiS2), group 6 (MoS2, MoSe2, WS2, and WSe2) and group 10 (PtS2, PtSe2 and PtTe2). Correlations between structures, properties as well as biosensing capabilities were elucidated from extensive characterisation data and electrochemical experiments. At the same time, strategies relevant to the compounds were simultaneously explored to enhance their conductivity. They were phase engineering, doping and electrochemical pretreatment. The superior material from each group of TMDs was developed into electrochemical biosensors with key analytical parameters established, prior to a comparison against other developed biosensors in literature. In parallel, this thesis aimed to leverage the advantages of 3D printing to fabricate a fundamental electrochemical component, the reference electrode. It was a straightforward process to 3D print the electrodes, subsequently modifying them to obtain Ag/AgCl pseudo-reference electrodes. Their electrochemical feasibility was studied in heterogeneous electron transfer reactions using different redox systems. With the advent of 3D printing, there are limitless opportunities for customisation of electrochemical devices as well as remote testing.